2006
DOI: 10.1111/j.1365-313x.2006.02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of an alfalfa cyclin‐dependent kinase inhibitor by calmodulin‐like domain protein kinase

Abstract: SummaryKip-related proteins (KRPs) play a central role in the regulation of the cell cycle and differentiation through modulation of cyclin-dependent kinase (CDK) functions. We have identified a CDK inhibitor gene from Medicago truncatula (Mt) by a yeast two-hybrid screen. The KRPMt gene was expressed in all plant organs and cultured cells, and its transcripts accumulated after abscisic acid and NaCl treatment. The KRPMt protein exhibits seven conserved sequence domains and a PEST motif that is also detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 59 publications
(164 reference statements)
0
52
0
Order By: Relevance
“…Previous work indicated a possible role for KRPs in stress response regulation. In Arabidopsis, KRP1 is known to respond to ABA (Wang et al, 1998), and an alfalfa KRP was induced both after mild salt treatment and ABA application (Pettko-Szandtner et al, 2006). Finally, we show a possible involvement of transcriptional regulation of the E2F/DP/RBR pathway in mediating responses to environmental conditions.…”
Section: Transcriptional Analysis Of Cell Cycle Genes Under Environmementioning
confidence: 78%
See 1 more Smart Citation
“…Previous work indicated a possible role for KRPs in stress response regulation. In Arabidopsis, KRP1 is known to respond to ABA (Wang et al, 1998), and an alfalfa KRP was induced both after mild salt treatment and ABA application (Pettko-Szandtner et al, 2006). Finally, we show a possible involvement of transcriptional regulation of the E2F/DP/RBR pathway in mediating responses to environmental conditions.…”
Section: Transcriptional Analysis Of Cell Cycle Genes Under Environmementioning
confidence: 78%
“…Mild salt stress leads to loss of CDK activity and to reduced promoter activity of CYCB1;2 (West et al, 2004). Finally, the production of a CDK activity inhibitor, KIP-related protein (KRP), is stimulated by abscisic acid (ABA) in Arabidopsis (KRP1) and alfalfa (Medicago sativa; KRPMt), suggesting a role for this gene in the ABA-mediated stress response pathway (Wang et al, 1998;Pettko-Szandtner et al, 2006).…”
mentioning
confidence: 99%
“…Based on our hypothesis that CDKA;1 is assisted by B-type CDKs during mitosis, one would expect weak ICK/KRP misexpression plants to have reduced rather than increased levels of endoreplication. However, the preference of ICK/KRPs to A-type CDKs is restricted to yeast two-hybrid data, and strikingly, a recent report using purified CDK complexes and adding ICK/KRP to them found that a B-type CDK complex was most susceptible to CKIs (Pettko-Szandtner et al, 2006). Thus, it will be an important task in the future to decipher the full spectrum of ICK/KRP targets.…”
Section: Low Cdk Activity and Plant Developmentmentioning
confidence: 99%
“…Earlier reports also showed that various stresses can induce cell cycle inhibitors of the CDK inhibitor (ICK)/KRP or SIM family and thereby arrest the cell cycle (Wang et al, 1998;Pettkó-Szandtner et al, 2006;De Veylder et al, 2007;Peres et al, 2007). Furthermore, DELLAs appear to be able to control cell proliferation rates by regulating KRP2, SIM, SIM-RELATED1 (SMR1), and SMR2 transcription (Achard et al, 2009).…”
mentioning
confidence: 99%